Designing Supramoleculer Materials via Click Chemistry: Liquid-Crystalline Dendrimers and Liquid-Crystalline Gold Nanoparticles - (:unkn) unknown (My University, 2025)
La synthèse de matériaux polyfonctionnels dotés de propriétés chimiques et physiques précises requière l'utilisation d'outils de synthèse performants. Il faut également que les unités fonctionnelles ne soient pas touchées lors des transformations. Une réaction qui a fait ses preuves est la "réaction click". Cette réaction permet d'obtenir des triazoles à partir de dérivés azotures et acétyléniques avec de très bons rendements. De plus, aucun produit secondaire ne se forme lors de cette réaction. Nous avons donc décidé d'appliquer cette réaction pour l'élaboration de matériaux macromoléculaires liquides-cristallins. Dans la première partie de notre projet, la "réaction click" sera utilisée pour synthétiser des dendrimères mésomorphes. Deux stratégies seront suivies: la "réaction click" sera utilisée pour assembler deux dendrons mésomorphes et pour faire croître le dendrimères. Dans le premier cas, la fonction triazole sera localisée au centre du dendrimère et, dans le second cas, les fonctions triazole seront localisées dans les ramifications du dendrimère. Grâce à la "réaction click", des dendrimères liquides-cristallins possédant des propriétés d'auto-organisation taillées sur mesure seront accessibles. Il sera également possible de mettre en évidence la relation entre la structure du composé et son organisation dans l'état liquide-cristallin. Dans la seconde partie de notre projet, nous utiliserons la "réaction click" pour fonctionnaliser des nanoparticules d'or avec des dendrimères liquides-cristallins, le but étant d'obtenir des métamatériaux. La "réaction click" sera une transformation des plus intéressantes pour greffer différents types de dendrons autour des nanoparticules d'or. Il sera possible de mettre en évidence la relation entre la structure et l'organisation supramoléculaire. Concevoir des macromolécules ayant des propriétés physiques et chimiques modulables par le biais de l'organisation supramoléculaire, elle-même contrôlable en fonction des dendrons utilisés, conduira, sans aucun doute, à des matériaux intéressants pour le développement des nanotechnologies. This proposal is devoted to the synthesis and study of supramolecular materials, the design of which is based on the versatile Huisgen 1,3-dipolar cycloaddition of azides and alkynes (click reaction). We would like to develop new strategies, new concepts to synthesize anisotropic materials which can be useful for the development of nanotechnologies by the "bottom-up" approach. The first part of the proposal (Section 2.3.1.) is devoted to the synthesis and study of liquid-crystalline dendrimers, the growth of which is controlled by the click reaction. The click reaction should become a reaction of choice for the synthesis of a great variety of liquid-crystalline dendrimers. Indeed, owing to the fact that the click reaction tolerates many different reaction conditions, the latter should be easily adapted to many different structural motives. The design and study of liquid-crystalline dendrimers is an important research area. The design of sophisticated liquid-crystalline dendrimers which display precise properties and functions requires the use of highly perfomant chemical reactions. This part of the proposal will bring results in this direction. The second part of the proposal (Section 2.3.2.) is devoted to the synthesis and study of giant liquid-crystalline dendrimers. Such materials are not easy to obtain by direct synthesis because of steric constraints on the dendrimer surface. Therefore, we would like to attach liquid-crystalline dendrons of different generations around a [60]fullerene unit which contains 12 azide goups. Addition reaction of the azide groups with alkyne-based dendrons via the click reaction will allow to attach 12 dendrons around a focal point. A huge increase in size will be obtained on going from the dendrons to the fullerodendrimers. Indeed, if the starting dendron has 8 mesogenic groups (for example), the final materials will have 96 (12 x 8) mesogenic groups ! Novel organizations are expected from such giant molecules. The third part of the proposal (Section 2.3.3.) is devoted to the synthesis and study of liquid-crystalline gold nanoparticles. Hybrid organic-inorganic nanoparticles are important to design materials with new properties. Of even more interest, are the nanoparticles which can self-organize into specific organizations. We would like to attach liquid-crystalline dendrons on the surfae of gold nanoparticles via the click reaction. With this methodology, we will be able to functionalize gold nanoparticles with a great variety of liquid-crystalline dendrons. This is the first step toward the development of liquid-crystalline nanoparticles with tailored-made mesomorphic properties. All dendrons and dendrimers will be synthesized via convergent and iterative synthetic routes; therefore, well-defined, monodisperse macromolecules will be obtained.
Keywords: supramolecular chemistry; click chemistry; dendrimers; fullerene; liquid crystals; self-organization; gold nanoparticles; nanoparticles; liquid